Glutamine and glutamic acid supplementation enhances performance of broiler chickens under the hot and humid tropical condition - Olubodun, Joshua O.; Idrus, Zulkifli; Farjam, Abdoreza Soleimani; Hair-Bejo, Mohd; Kasim, Azhar (PAGEPress, 2015)
Day-old (day 1) commercial broiler chickens were fed i) basal diet (control), ii) basal diet +0.5% AminoGut (AG), or iii) basal diet +1% AG from 1 to 42 d of age under the hot and humid tropical environment. AminoGut is a commercial dietary supplement containing a mixture of L-glutamine (Gln) and L-glutamic (Glu) acid. Weight gain and feed conversion ratio during the starter (1 to 21 d) and overall (1 to 42 d) periods improved linearly and quadratically with AG supplementation when compared to control. Supplementing birds with AG significantly reduced overall mortality rate. At 21 and 42 d of age, intestinal (duodenum and ileum) villi height and crypt depth showed both linear and quadratic positive responses to AG supplementation. Intestinal amylase activity increased linearly and quadratically on d 21, and linearly only on d 42. In conclusion, Gln and Glu supplementation was beneficial in improving the growth performance and survivability of broiler chickens under the hot and humid tropical environment.